SYSTEMATIC REVIEW ON MAJOR DEPRESSIVE DISORDER AND COGNITIVE BEHAVIORAL THERAPY - ÇAKAL , Kardelen; KARAAZİZ , Meryem (SSD Journal, 2023)
Depression manifests itself as a picture of a disease that leads to sudden decreases in mood or behavior. Although the reactions of each individual to the disease are different, it puts a person in a difficult situation from a spiritual point of view. CBT, on the other hand, is characterized as a psychotherapeutic approach aimed at solving problems related to dysfunctional behaviors, emotions, attitudes and cognition by systematic procedure, being a widely researched model of treatment effectiveness of emotional and behavioral problems. In this study, the relationship between major depression and cognitive behavioral therapy is discussed. Dec. The aim of this review study is to examine the use of CBT in individuals with MDD. The systematic review method was used in the study and no field study or any scale was used. Turkish English and Turkish language studies are being Deciphered between the years 2009-2023. These studies consist of experimental, semi-experimental studies. As a result of the literature review, 6 studies were considered. As a result of the 6 studies considered, it has been determined that CBT is an effective treatment method for major depression disorder. It has been found that in individuals with MDD, symptoms decrease at a high rate and disappear completely immediately after CBT administration. For this reason, it seems that MDB treatment is an effective method in CBT therapy, and since research on CBT and MDB is limited, it is recommended to support it with more up-to-date research in the field and contribute to the literature